Early management for traumatic benign paroxysmal positional vertigo in traumatically injured patients. Issue 1 (January 2022) - Kim, Hantai; Ha, Jungho; Lee, Ju Ho; Jang, Jeong Hun; Park, Hun Yi; Choung, Yun-Hoon
Highlights: Since it is difficult to suspect BPPV on clinical symptoms, diagnostic maneuvers should be actively performed in injured patients with vertigo. 'Passenger car accident' and 'slip-down injury' were more common in mild BPPV, and 'a fall' and 'pedestrian car accident' was more in severe BPPV. Early management with prompt canalith repositioning procedures is a significant factor affecting the progress of BPPV. In the traumatically injured patients, the possibility of spontaneous resolution of BPPV might be lower due to their immobilized status. Canalith repositioning procedures may be the only treatment option for the injured patients, so active and early management is recommended. Abstract: Objectives: The purpose of this study was to identify the clinical features of posttraumatic benign paroxysmal positional vertigo (t-BPPV) in traumatically injured patients, investigating the effectiveness of the early diagnosis and management including canalith repositioning procedures (CRPs). Patients and methods: The subjects of the present study were 74 patients who were hospitalized in the Trauma Center, Ajou University Hospital. We investigated the relationship between injury mechanisms and t-BPPV. Patients with t-BPPV were categorized into mild (typical BPPV) and severe (bilateral, recurrent, or persistent) types. Results: Of the 74 patients, 41 were diagnosed with t-BPPV. Nineteen were mild and 22 were severe types. 'A fall' (36%) and 'pedestrian car accident' (32%) were common as the injury mechanisms provoking severe t-BPPV. In the severe t-BPPV group, they were hospitalized longer (as median value, 20 days in the severe group vs. 10 days in the mild group, P = 0.004), stayed longer in intensive care unit (3 days vs. 0 days, P = 0.016), and needed more days until the BPPV management (13.5 days vs. 6 days, P = 0.021). Major trauma (the Injury Severity Score >15) patients had a longer time to implementation of the first CRPs (10 days in major trauma and 3 days in minor trauma patients, P = 0.019). Conclusions: Severity of trauma and longer duration of ICU treatment were factors delaying BPPV management. This delay could negatively affect the progress of t-BPPV. Diagnostic and therapeutic maneuvers including CRPs should be performed as early as possible, even in severely injured patients.